A health promotion approach to reducing stigma and discrimination : a framework for action - O'Neil, Cheryl (Caribbean Epidemiology Centre /PAHO/WHO Port of SpainTT, 2004)
Looks at ways of formulating healthy public policy, reorienting health services and empowering communities - to achieve well being. Focuses on creating a supportive environment, developing/increasing personal health skills, and building alliances with special emphasis on the media.